Hệ thống quản lý lưu trình công việc và bản tin trên mạng WAN - Tam, Nguyễn Văn (Journal of Computer Science and Cybernetics, 2016)
In this paper we present the design and implementation of system of workflow and news management by using integrated Microsoft software. This presentation includes the design of concentrated and distributed models and databases. Using integrated Microsoft utilities yields benefit for system such as: open, ease to use, security.